A kind of mildew-proof environmentally friendly glass glue and preparation method thereof

By using carboxymethyl chitosan Schiff base nanomodified castor oil-based aqueous polyurethane prepolymer emulsion and titanium dioxide nanocomposite hydrogel in glass glue, the problem of polyurethane glass glue being prone to mildew is solved, achieving efficient anti-mold effect and environmentally friendly performance.

CN119242252BActive Publication Date: 2025-03-18SHANDONG JIAOBAO NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411776142.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing polyurethane glass glue is prone to mildew after being used for a period of time, resulting in color changes and aesthetic problems. At the same time, the use of petroleum-based raw materials is harmful to the environment and health.

Method used

Carboxymethyl chitosan Schiff base nanomodified castor oil-based aqueous polyurethane prepolymer emulsion is used as the main component, and titanium dioxide nanocomposite hydrogel is added as the anti-mold agent to the glass glue. By combining the modifier and the nanocomposite material, the anti-mold performance of the glass glue is improved.

Benefits of technology

It significantly improves the anti-mold effect of glass glue and can maintain good anti-mold performance within 56 days. At the same time, due to the use of bio-based raw materials and nanomaterials, the environmental protection performance and safety of glass glue have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention belongs to the technical field of glass glue, and specifically relates to a mildew-proof and environmentally friendly glass glue and a preparation method thereof. The glass glue comprises the following components by weight percentage: 60-65% of carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion, 8-10% of mildew inhibitor, 5-5.5% of plasticizer, 0.04-0.1% of defoamer and 20-26% of filler. The carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion is obtained by modifying castor oil-based waterborne polyurethane prepolymer with carboxymethyl chitosan Schiff base nanomaterial. The invention performs chain extension modification on castor oil-based waterborne polyurethane prepolymer by carboxymethyl chitosan Schiff base, thereby improving the mildew resistance of castor oil-based waterborne polyurethane prepolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass glue, and in particular relates to mildew-proof and environmentally friendly glass glue and a preparation method thereof. Background Art

[0002] Glass cement, also known as glass cement, is a common adhesive used for sealing and modification in construction, automobiles and daily life. Glass cement is a general term, and both silicone glue and polyurethane glue can be commonly called glass cement.

[0003] Polyurethane glass glue has excellent performance and adjustability and is widely used. However, the main raw materials of polyurethane glass glue, isocyanate and polyol, usually come from non-renewable petroleum resources. On the one hand, the use of fossil raw materials such as petroleum-based and coal will release a large amount of carbon dioxide and a variety of volatile organic compounds, which are harmful to the environment and human health. Therefore, from the environmental and economic perspectives, the development of renewable raw materials as a green alternative to fossil raw materials has become an urgent problem to be solved.

[0004] On the other hand, the normal form of glass glue after construction is colloid, but after a period of use, it will often turn black or discolor. This is because the kitchen and bathroom environment is humid and prone to breeding mold. After mold, the places with glass glue will turn black or discolor, affecting the appearance. After mold, it will breed bacteria, which will not only affect the appearance but also threaten human health. Summary of the invention

[0005] The object of the present invention is to provide a mildew-proof and environmentally friendly glass glue and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to achieve the above technical purpose, the technical solution of the present invention is:

[0007] A mildew-proof and environment-friendly glass adhesive comprises the following components by weight percentage: 60-65% of carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion, 8-10% of mildew inhibitor, 5-5.5% of plasticizer, 0.04-0.1% of defoamer and 20-26% of filler. The carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion is obtained by modifying castor oil-based waterborne polyurethane prepolymer with carboxymethyl chitosan Schiff base nanomaterial.

[0008] As a further improvement, the plasticizer is bisphenol A epoxy resin or bisphenol A-epoxy resin crosslinked product, the defoamer is polyethylene glycol, the filler is white carbon black, and the mildew inhibitor is titanium dioxide nanocomposite hydrogel.

[0009] The present invention also provides a method for preparing mildew-proof and environmentally friendly glass glue, comprising the following steps:

[0010] S1, preparation of carboxymethyl chitosan Schiff base nano-modifier;

[0011] Dissolve carboxymethyl chitosan in distilled water to prepare a 10 mg / mL carboxymethyl chitosan aqueous solution, slowly add a dimethyl sulfoxide solution of dicyclohexylcarbodiimide and a dimethyl sulfoxide solution of 4-dimethylaminopyridine to the carboxymethyl chitosan aqueous solution, activate at 60° C. for 1 hour, then slowly add a bio-based Schiff base dimethyl sulfoxide solution thereto, react at 60° C. in the dark for 4 hours, after the reaction is completed, add 100 mL of acetone solution, keep it in the dark for 3 hours, take the precipitate, wash it with acetone for 5 times, and then vacuum dry it to obtain a carboxymethyl chitosan Schiff base nano-modifier;

[0012] S2, preparation of carboxymethyl chitosan Schiff base modified castor oil based waterborne polyurethane prepolymer emulsion;

[0013] Castor oil was added into a round-bottom four-necked flask, vacuum-dehydrated at 100-120°C, cooled to 60°C under nitrogen protection, isophorone diisocyanate was added thereto, reacted for 20 minutes, dimethylol propionic acid and dibutyltin dilaurate were added into the four-necked flask, the reaction system was heated to 80-90°C, reacted for 3 hours, then the reaction system was cooled to 40°C, acetone was added to reduce the viscosity, then carboxymethyl chitosan Schiff base nano-modifier aqueous solution was added into the four-necked flask, the temperature was raised to 60°C and reacted for 5 hours, then triethylamine was added into the four-necked flask to neutralize the polymerization system until the pH value of the system was maintained at 7-8, then 50 mL of distilled water was added and stirred at high speed for emulsification for 1 hour, and the solvent in the system was removed by a rotary evaporator to obtain a carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion;

[0014] S3. Remove moisture from the filler at a constant temperature of 120°C, then add carboxymethyl chitosan Schiff base nano-modified castor oil-based water-based polyurethane emulsion, mildew inhibitor, plasticizer, filler and defoamer into a stirrer, and stir for 15 minutes under vacuum conditions to obtain mildew-proof and environmentally friendly glass glue.

[0015] As a further improvement, in step S1, the concentration of dicyclohexylcarbodiimide in the dimethyl sulfoxide solution of dicyclohexylcarbodiimide is 4 mg / mL, and the concentration of 4-dimethylaminopyridine in the dimethyl sulfoxide solution of 4-dimethylaminopyridine is 2 mg / mL.

[0016] As a further improvement, in step S1, the preparation method of the bio-based Schiff base dimethyl sulfoxide solution is: take 0.72g of ethylenediamine and 1.83g of vanillin and dissolve them in a sodium hydroxide solution with a pH of 10, react at 25°C for 24h, then add 1mol / L HCl to the solution to adjust the pH to 7, then centrifuge at 4000r / min for 5min, collect the supernatant, vacuum distill to remove water, repeatedly wash, and extract with chloroform to remove impurities, and the obtained solid is vacuum dried at 60°C for 48h, and then the dried solid is dissolved in 20mL of dimethyl sulfoxide to obtain a bio-based Schiff base dimethyl sulfoxide solution.

[0017] As a further improvement, in step S2, n -NCO / n -OH =1.4.

[0018] As a further improvement, in step S2, the mass ratio of the added dimethylolpropionic acid to the castor oil is 0.14:1, and the added amount of the dibutyltin dilaurate is 3 mL.

[0019] As a further improvement, the preparation method of the titanium dioxide nanocomposite hydrogel is as follows: under nitrogen protection, deionized water is poured into a three-necked round-bottom flask, and then N-isopropylacrylamide, acrylic acid, and acrylamide are added to the round-bottom flask in sequence, and after mixing evenly, a crosslinking agent N,N'-methylenebisacrylamide and a catalyst tetramethylethylenediamine are added. After the solution in the round-bottom flask is stirred and mixed evenly, titanium dioxide is slowly added to the round-bottom flask under light-shielding conditions, stirred for 1 hour, and then potassium persulfate is added to the round-bottom flask to allow the system to undergo a free radical polymerization reaction. After reacting for 6 hours, the reacted solution is placed in a dialysis bag and dialyzed with deionized water for 7 days, with the water changed 3 times a day, to obtain a titanium dioxide nanocomposite hydrogel.

[0020] In the present invention, the reaction equation for preparing the bio-based Schiff base is as follows:

[0021] ;

[0022] The reaction equation for preparing carboxymethyl chitosan Schiff base nano-modifier is as follows:

[0023] ;

[0024] The reaction equation for preparing carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion is as follows:

[0025] ;

[0026] .

[0027] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] The present invention provides a mildew-proof and environmentally friendly glass glue. A castor oil-based waterborne polyurethane prepolymer is chain-extended and modified by a carboxymethyl chitosan Schiff base nano-modifier, thereby improving the mildew resistance of the castor oil-based waterborne polyurethane prepolymer. Titanium dioxide nano-composite hydrogel is added to the glass glue as a mildew-proof agent, thereby further improving the mildew-proof effect of the glass glue. According to a mildew resistance test, the glass glue prepared in the present invention can still achieve a very good mildew-proof effect after 56 days.

[0029] The present invention adopts castor oil as a bio-based polyol raw material, and the prepared waterborne polyurethane prepolymer is more environmentally friendly. The carboxymethyl chitosan has biodegradability and biocompatibility, and does not produce substances harmful to the environment. The raw materials used in the carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion prepared by the present invention and the raw materials used in the use process are more environmentally friendly.

[0030] The peeling strength of the glass glue prepared by the present invention is similar to that of the glass glue using castor oil-based waterborne polyurethane prepolymer emulsion as the main agent, and the use effect is also very good. DETAILED DESCRIPTION

[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] Example 1 This example provides a mildew-proof and environmentally friendly glass glue, which includes the following components by weight percentage: 65% of carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 8% mildewproof agent, 5% plasticizer, 0.04% defoaming agent and 21.96% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is bisphenol A epoxy resin.

[0033] The method for preparing the mildew-proof and environmentally friendly glass glue of this embodiment comprises the following steps:

[0034] S1. Preparation of bio-based Schiff base dimethyl sulfoxide solution;

[0035] 0.72 g of ethylenediamine and 1.83 g of vanillin were dissolved in a sodium hydroxide solution with a pH of 10, and reacted at 25°C for 24 h. Then, 1 mol / L HCl was added to the solution to adjust the pH to 7. The solution was then centrifuged at 4000 r / min for 5 min, the supernatant was collected, and the water was removed by vacuum distillation. After repeated washing, impurities were removed by extraction with chloroform. The obtained solid was vacuum dried at 60°C for 48 h. The dried solid was then dissolved in 20 mL of dimethyl sulfoxide to obtain a bio-based Schiff base dimethyl sulfoxide solution.

[0036] S2, preparation of carboxymethyl chitosan Schiff base nano-modifier;

[0037] 100 mg of carboxymethyl chitosan was dissolved in 10 mL of distilled water to prepare a 10 mg / mL carboxymethyl chitosan aqueous solution, 40 mg of dicyclohexylcarbodiimide was weighed and dissolved in 10 mL of dimethyl sulfoxide solution to obtain a 4 mg / mL dicyclohexylcarbodiimide dimethyl sulfoxide solution, and 20 mg of 4-dimethylaminopyridine was weighed and dissolved in 10 mL of dimethyl sulfoxide solution to obtain a 2 mg / mL 4-dimethylaminopyridine dimethyl sulfoxide solution;

[0038] Then, the dimethyl sulfoxide solution of dicyclohexylcarbodiimide and the dimethyl sulfoxide solution of 4-dimethylaminopyridine are slowly added to the carboxymethyl chitosan aqueous solution, activated at 60° C. for 1 hour, and then the bio-based Schiff base dimethyl sulfoxide solution is slowly added thereto, reacted at 60° C. in the dark for 4 hours, after the reaction is completed, 100 mL of acetone solution is added, and the mixture is allowed to stand in the dark for 3 hours, the precipitate is washed with acetone for 5 times, and then vacuum dried to obtain a carboxymethyl chitosan Schiff base nano-modifier;

[0039] S3, preparation of carboxymethyl chitosan Schiff base modified castor oil based waterborne polyurethane prepolymer emulsion;

[0040] 10g of castor oil was added to a round-bottom four-necked flask, and after vacuum dehydration at 100°C, the temperature was lowered to 60°C under nitrogen protection, and 4.52g of isophorone diisocyanate was added thereto. After reacting for 20min, 1.4g of dihydroxymethylpropionic acid and 3mL of dibutyltin dilaurate were added to the four-necked flask, the reaction system was heated to 80°C and reacted for 3h, and then the reaction system was cooled to 40°C, and acetone was added to reduce the viscosity, and then the prepared carboxymethyl chitosan Schiff base nano-modifier aqueous solution was added to the four-necked flask, the temperature was raised to 60°C and reacted for 5h, and then 1.014g of triethylamine was added to the four-necked flask to neutralize the polymerization system until the pH value of the system was maintained at 7-8, and then 50mL of distilled water was added and stirred at high speed for emulsification for 1h, and the solvent in the system was removed by a rotary evaporator to obtain a carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion, wherein n -NCO / n-OH =1.4;

[0041] S3, preparation of titanium dioxide nanocomposite hydrogel;

[0042] Under nitrogen protection, 100 mL of deionized water was poured into a three-necked round-bottom flask, and then 0.628 g of N-isopropylacrylamide, 25 μL of acrylic acid, and 0.035 g of acrylamide were added to the round-bottom flask in sequence. After mixing evenly, 170 μL of a cross-linking agent N, N'-methylenebisacrylamide and 93 μL of a catalyst tetramethylethylenediamine were added. After the solution in the round-bottom flask was stirred and mixed evenly, 1.6 mg of titanium dioxide was slowly added to the round-bottom flask under light-shielding conditions, stirred for 1 h, and then 1 mL of potassium persulfate was added to the round-bottom flask to allow the system to undergo a free radical polymerization reaction. After reacting for 6 h, the reacted solution was placed in a dialysis bag and dialyzed with deionized water for 7 days, with the water changed 3 times a day to obtain a titanium dioxide nanocomposite hydrogel.

[0043] S4. Remove moisture from the filler at a constant temperature of 120°C, then add carboxymethyl chitosan Schiff base nano-modified castor oil-based water-based polyurethane emulsion, mildew inhibitor, plasticizer and defoamer into a stirrer, and stir for 15 minutes under vacuum conditions to obtain mildew-proof and environmentally friendly glass glue.

[0044] In this embodiment, during the preparation of carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion, n -NCO / n -OH Select 1.4, n -NCO / n -OH is the ratio of the amount of -NCO in isophorone diisocyanate to the amount of -OH in castor oil. The hydroxyl value of castor oil in this example is 163 mgKOH / g.

[0045] Example 2 This example provides a mildew-proof and environmentally friendly glass glue, which includes the following components by weight percentage: 60% carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 10% mildewproof agent, 5.5% plasticizer, 0.1% defoaming agent and 24.4% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0046] The preparation method of the mildew-proof and environmentally friendly glass glue of this embodiment specifically comprises the following steps:

[0047] S1. Preparation of bio-based Schiff base dimethyl sulfoxide solution;

[0048] 0.72 g of ethylenediamine and 1.83 g of vanillin were dissolved in a sodium hydroxide solution with a pH of 10, and reacted at 25°C for 24 h. Then, 1 mol / L HCl was added to the solution to adjust the pH to 7. The solution was then centrifuged at 4000 r / min for 5 min, the supernatant was collected, and the water was removed by vacuum distillation. After repeated washing, impurities were removed by extraction with chloroform. The obtained solid was vacuum dried at 60°C for 48 h. The dried solid was then dissolved in 20 mL of dimethyl sulfoxide to obtain a bio-based Schiff base dimethyl sulfoxide solution.

[0049] S2, preparation of carboxymethyl chitosan Schiff base nano-modifier;

[0050] 100 mg of carboxymethyl chitosan was dissolved in 10 mL of distilled water to prepare a 10 mg / mL carboxymethyl chitosan aqueous solution, 40 mg of dicyclohexylcarbodiimide was weighed and dissolved in 10 mL of dimethyl sulfoxide solution to obtain a 4 mg / mL dicyclohexylcarbodiimide dimethyl sulfoxide solution, and 20 mg of 4-dimethylaminopyridine was weighed and dissolved in 10 mL of dimethyl sulfoxide solution to obtain a 2 mg / mL 4-dimethylaminopyridine dimethyl sulfoxide solution;

[0051] Then, the dimethyl sulfoxide solution of dicyclohexylcarbodiimide and the dimethyl sulfoxide solution of 4-dimethylaminopyridine are slowly added to the carboxymethyl chitosan aqueous solution, activated at 60° C. for 1 hour, and then the bio-based Schiff base dimethyl sulfoxide solution is slowly added thereto, reacted at 60° C. in the dark for 4 hours, after the reaction is completed, 100 mL of acetone solution is added, and the mixture is allowed to stand in the dark for 3 hours, the precipitate is washed with acetone for 5 times, and then vacuum dried to obtain a carboxymethyl chitosan Schiff base nano-modifier;

[0052] S3, preparation of carboxymethyl chitosan Schiff base modified castor oil based waterborne polyurethane prepolymer emulsion;

[0053] 10g of castor oil was added to a round-bottom four-necked flask, and after vacuum dehydration at 120°C, the temperature was lowered to 60°C under nitrogen protection, and 4.52g of isophorone diisocyanate was added thereto. After reacting for 20min, 1.4g of dihydroxymethylpropionic acid and 3mL of dibutyltin dilaurate were added to the four-necked flask, the reaction system was heated to 90°C and reacted for 3h, and then the reaction system was cooled to 40°C, and acetone was added to reduce the viscosity, and then the above-prepared carboxymethyl chitosan Schiff base nano-modifier aqueous solution was added to the four-necked flask, the temperature was raised to 60°C and reacted for 5h, and then 1.014g of triethylamine was added to the four-necked flask to neutralize the polymerization system until the pH value of the system was maintained at 7-8, and then 50mL of distilled water was added and stirred at high speed for emulsification for 1h, and the solvent in the system was removed by a rotary evaporator to obtain a carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion, wherein n -NCO / n-OH =1.4;

[0054] S3, preparation of titanium dioxide nanocomposite hydrogel;

[0055] Under nitrogen protection, 100 mL of deionized water was poured into a three-necked round-bottom flask, and then 0.628 g of N-isopropylacrylamide, 25 μL of acrylic acid, and 0.035 g of acrylamide were added to the round-bottom flask in sequence. After mixing evenly, 170 μL of a cross-linking agent N, N'-methylenebisacrylamide and 93 μL of a catalyst tetramethylethylenediamine were added. After the solution in the round-bottom flask was stirred and mixed evenly, 1.6 mg of titanium dioxide was slowly added to the round-bottom flask under light-shielding conditions, stirred for 1 h, and then 1 mL of potassium persulfate was added to the round-bottom flask to allow the system to undergo a free radical polymerization reaction. After reacting for 6 h, the reacted solution was placed in a dialysis bag and dialyzed with deionized water for 7 days, with the water changed 3 times a day to obtain a titanium dioxide nanocomposite hydrogel.

[0056] S4. Remove moisture from the filler at a constant temperature of 120°C, then add carboxymethyl chitosan Schiff base nano-modified castor oil-based water-based polyurethane emulsion, mildew inhibitor, plasticizer and defoamer into a stirrer, and stir for 15 minutes under vacuum conditions to obtain mildew-proof and environmentally friendly glass glue.

[0057] In this embodiment, during the preparation of carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion, n -NCO / n -OH Select 1.4, n -NCO / n -OH is the ratio of the amount of -NCO in isophorone diisocyanate to the amount of -OH in castor oil. The hydroxyl value of castor oil in this example is 163 mgKOH / g.

[0058] Example 3 This example provides a mildew-proof and environmentally friendly glass glue, which includes the following components by weight percentage: 60% carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 8.63% mildewproof agent, 5.3% plasticizer, 0.07% defoaming agent and 26% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0059] Example 4 This example provides a mildew-proof and environmentally friendly glass glue, which includes the following components by weight percentage: 64.9% of carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 10% mildewproof agent, 5% plasticizer, 0.1% defoaming agent and 20% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0060] Example 5 This example provides a mildew-proof and environmentally friendly glass glue, which includes the following components by weight percentage: 63% carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 9% mildewproof agent, 5% plasticizer, 0.1% defoaming agent and 22.9% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0061] Comparative Example 1 This comparative example provides a glass glue, which includes the following components by weight percentage: 60% castor oil-based water-based polyurethane prepolymer emulsion, 10% mildewproof agent, 5.5% plasticizer, 0.1% defoaming agent and 24.4% filler, wherein the mildewproof agent is titanium dioxide nano-composite hydrogel, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0062] Comparative Example 2 This comparative example provides a glass glue, which includes the following components by weight percentage: 60% carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 10% mildewproof agent, 5.5% plasticizer, 0.1% defoaming agent and 24.4% filler, wherein the mildewproof agent is KP-M23, the filler is white carbon black, the defoaming agent is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0063] Comparative Example 3 This comparative example provides a glass glue, which includes the following components by weight percentage: 60% carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion, 8% ethanol, 5.5% plasticizer, 0.1% defoamer and 24.4% filler, and 2% water, wherein the filler is white carbon black, the defoamer is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0064] Comparative Example 4 This comparative example provides a glass glue, which includes the following components by weight percentage: 60% castor oil-based water-based polyurethane prepolymer emulsion, 8% ethanol, 5.5% plasticizer, 0.1% defoamer and 24.4% filler, and 2% water, wherein the filler is white carbon black, the defoamer is polyethylene glycol, and the plasticizer is diphenol A-epoxy resin crosslinked product.

[0065] Example 6 The 180° peel strength of the glass adhesives prepared in Example 1 and Comparative Examples 1-4 was tested according to the GB / T2792-1998 test standard. The experimental results are shown in Table 1.

[0066]

[0067] Example 7 This example tests the fungus resistance of the glass glue obtained in Example 1 and Comparative Examples 1-4. The main method is as follows:

[0068] For sample preparation, five glass plates with a size of 25 cm × 30 cm and a thickness of 1 mm were taken, the surfaces were cleaned with acetone, and then the surfaces were dried with a hot air stream, and the glass glue obtained in Example 1 and Comparative Examples 1-4 were applied to the surfaces of the five glass plates respectively, and cured at room temperature for 7 days. After the curing was completed, the samples were cut into a size of 50 mm × 50 mm.

[0069] Aspergillus niger, Aspergillus flavus, Paecilomyces variotii, Penicillium citrinum, Trichoderma viride, Aureobasidium bracteata, Aspergillus terreus, and Penicillium funiculum were selected as experimental strains. The above 8 test strains were inoculated on the same PDA medium and cultured at 28°C for 7 days to make the surface of the medium full of spores. Then 10 mL of sterile water was added, and the spores were scraped off with a sterile inoculation loop to make a mixed spore suspension. The mixed spore suspension was added to a triangular flask with glass beads and sterile water, and the spores were fully released after vigorous shaking, and then filtered to remove hyphae and culture medium fragments. The filtered spore suspension was centrifuged at a speed of 4000 r / min for 10 min, and sterile water was added to mix after removing the supernatant. After centrifugation twice, the mixed spore suspension was obtained and diluted with a nutrient salt solution to make the concentration of the inoculated spore liquid 8×10 5 Pieces / mL.

[0070] The prepared glass samples were placed under ultraviolet light for 20 minutes for sterilization. The treated samples were placed on culture dishes containing nutrient salt agar medium, and then 0.5 mL of 8×10 5 The mixed spore suspension of 100 / mL was used to wet the entire surface of the glass sample.

[0071] The inoculated glass sample culture dish was placed in a constant temperature and humidity incubator. After culturing for 7 days at a temperature of 25°C and a relative humidity of 85%, the culture medium was observed to see if there was mold growth. The culture was then continued for 28 days, and the percentage of moldy area of ​​the sample was determined and the results were graded. The culture was continued for 56 days, and the percentage of moldy area of ​​the sample was determined again and the results were graded. Table 2 is a grading evaluation table for mold resistance.

[0072]

[0073] As shown in Table 3, the test results of the mildew resistance test of Example 1 and Comparative Examples 1-4 for 28 days in this embodiment are shown, and Table 4 is the test results of the mildew resistance test of Example 1 and Comparative Examples 1-4 for 56 days in this embodiment are shown.

[0074]

[0075]

[0076] It can be seen from Tables 3 and 4 that the glass glue prepared in Example 1 has the best mildew resistance effect, while the mildew resistance test results of the glass glue in Example 2 in which a common mildew resistance agent on the market is added and in Example 3 in which no mildew resistance agent is added are compared, and the difference in the proportion of mold growth area is not large, indicating that the carboxymethyl chitosan Schiff base modified castor oil-based water-based polyurethane prepolymer emulsion prepared in the present invention has a high efficiency mildew resistance effect as the main agent of glass glue, and by comparing the mildew resistance test results of Example 1 and Comparative Example 2, the mildew resistance agent titanium dioxide nanocomposite hydrogel prepared in this example further improves the mildew resistance effect of the glass glue in Example 1.

[0077] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A mildew-proof and environmentally friendly glass glue, characterized in that: The invention comprises the following components by weight percentage: 60-65% of carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion, 8-10% of mildew inhibitor, 5-5.5% of plasticizer, 0.04-0.1% of defoamer and 20-26% of filler, wherein the carboxymethyl chitosan Schiff base modified castor oil-based waterborne polyurethane prepolymer emulsion is obtained by modifying castor oil-based waterborne polyurethane prepolymer with carboxymethyl chitosan Schiff base nanomaterial; The preparation method of the carboxymethyl chitosan Schiff base nanomaterial is as follows: 0.72g of ethylenediamine and 1.83g of vanillin are dissolved in a sodium hydroxide solution with a pH of 10, reacted at 25°C for 24h, then 1mol / L of HCl is added to the solution to adjust the pH to 7, then centrifuged at a speed of 4000r / min for 5min, the supernatant is collected, water is removed by vacuum distillation, after repeated washing, impurities are removed by extraction with chloroform, the obtained solid is vacuum dried at 60°C for 48h, and then the dried solid is dissolved in 20mL of dimethyl sulfoxide to obtain the bio-based Schiff base dimethyl dissolving carboxymethyl chitosan in distilled water to obtain a 10 mg / mL carboxymethyl chitosan aqueous solution, slowly adding a dimethyl sulfoxide solution of dicyclohexylcarbodiimide and a dimethyl sulfoxide solution of 4-dimethylaminopyridine to the carboxymethyl chitosan aqueous solution, activating at 60° C. for 1 h, then slowly adding a bio-based Schiff base dimethyl sulfoxide solution thereto, reacting at 60° C. in the dark for 4 h, after the reaction is completed, adding 100 mL of acetone solution, standing in the dark for 3 h, taking the precipitate, washing it with acetone for 5 times, and then vacuum drying to obtain a carboxymethyl chitosan Schiff base nano-modifier.

2. The mildew-proof and environmentally friendly glass glue according to claim 1, characterized in that: The plasticizer is bisphenol A epoxy resin or bisphenol A-epoxy resin crosslinked product, the defoamer is polyethylene glycol, the filler is white carbon black, and the mildew preventer is titanium dioxide nanocomposite hydrogel.

3. The method for preparing the mildew-proof and environmentally friendly glass glue according to claim 2, characterized in that: The following steps are involved: S1, preparation of carboxymethyl chitosan Schiff base nano-modifier; Dissolve carboxymethyl chitosan in distilled water to prepare a 10 mg / mL carboxymethyl chitosan aqueous solution, slowly add a dimethyl sulfoxide solution of dicyclohexylcarbodiimide and a dimethyl sulfoxide solution of 4-dimethylaminopyridine to the carboxymethyl chitosan aqueous solution, activate at 60° C. for 1 hour, then slowly add a bio-based Schiff base dimethyl sulfoxide solution thereto, react at 60° C. in the dark for 4 hours, after the reaction is completed, add 100 mL of acetone solution, keep it in the dark for 3 hours, take the precipitate, wash it with acetone for 5 times, and then vacuum dry it to obtain a carboxymethyl chitosan Schiff base nano-modifier; The preparation method of the bio-based Schiff base dimethyl sulfoxide solution is as follows: 0.72g of ethylenediamine and 1.83g of vanillin are dissolved in a sodium hydroxide solution with a pH of 10, reacted at 25°C for 24h, then 1mol / L of HCl is added to the solution to adjust the pH to 7, then centrifuged at a speed of 4000r / min for 5min, the supernatant is collected, and water is removed by vacuum distillation. After repeated washing, impurities are removed by extraction with chloroform, and the obtained solid is vacuum dried at 60°C for 48h, and then the dried solid is dissolved in 20mL of dimethyl sulfoxide to obtain the bio-based Schiff base dimethyl sulfoxide solution; S2, preparation of carboxymethyl chitosan Schiff base modified castor oil based waterborne polyurethane prepolymer emulsion; Castor oil was added into a round-bottom four-necked flask, vacuum-dehydrated at 100-120°C, cooled to 60°C under nitrogen protection, isophorone diisocyanate was added thereto, reacted for 20 minutes, dimethylol propionic acid and dibutyltin dilaurate were added into the four-necked flask, the reaction system was heated to 80-90°C, reacted for 3 hours, then the reaction system was cooled to 40°C, acetone was added to reduce the viscosity, then carboxymethyl chitosan Schiff base nano-modifier aqueous solution was added into the four-necked flask, the temperature was raised to 60°C and reacted for 5 hours, then triethylamine was added into the four-necked flask to neutralize the polymerization system until the pH value of the system was maintained at 7-8, then 50 mL of distilled water was added and stirred at high speed for emulsification for 1 hour, and the solvent in the system was removed by a rotary evaporator to obtain a carboxymethyl chitosan Schiff base nano-modified castor oil-based waterborne polyurethane emulsion; S3. Remove moisture from the filler at a constant temperature of 120°C, then add carboxymethyl chitosan Schiff base nano-modified castor oil-based water-based polyurethane emulsion, mildew inhibitor, plasticizer, filler and defoamer into a stirrer, and stir for 15 minutes under vacuum conditions to obtain mildew-proof and environmentally friendly glass glue.

4. The method for preparing the mildew-proof and environmentally friendly glass glue according to claim 3, characterized in that: In step S1, in the dimethyl sulfoxide solution of dicyclohexylcarbodiimide, the concentration of dicyclohexylcarbodiimide is 4 mg / mL, and in the dimethyl sulfoxide solution of 4-dimethylaminopyridine, the concentration of 4-dimethylaminopyridine is 2 mg / mL.

5. The method for preparing the mildew-proof and environmentally friendly glass glue according to claim 3, characterized in that: In step S2, n -NCO / n -OH =1.

4.

6. The method for preparing the mildew-proof and environmentally friendly glass glue according to claim 3, characterized in that: In step S2, the mass ratio of the added dimethylolpropionic acid to the castor oil is 0.14:1, and the added amount of the dibutyltin dilaurate is 3 mL.

7. The method for preparing the mildew-proof and environmentally friendly glass glue according to claim 3, characterized in that: The preparation method of the titanium dioxide nanocomposite hydrogel is as follows: under nitrogen protection, deionized water is poured into a three-necked round-bottom flask, then N-isopropylacrylamide, acrylic acid, and acrylamide are added to the round-bottom flask in sequence, and after being evenly mixed, a crosslinking agent N,N'-methylenebisacrylamide and a catalyst tetramethylethylenediamine are added, and after the solution in the round-bottom flask is stirred and mixed evenly, titanium dioxide is slowly added to the round-bottom flask under light-shielding conditions, and stirred for 1 hour, and then potassium persulfate is added to the round-bottom flask to make the system undergo free radical polymerization reaction, and after reacting for 6 hours, the reacted solution is placed in a dialysis bag, and dialyzed with deionized water for 7 days, with the water changed 3 times a day, to obtain the titanium dioxide nanocomposite hydrogel.

Citation Information

Patent Citations

  • Antibacterial and weather-resistant polyurethane glass cement

    CN108084941A

  • Preparation method of ultraviolet-curable castor oil-based antimicrobial aqueous polyurethane emulsion

    CN110218440A